(untitled) (Sains Humanika, 2011)
The purpose of this study was to investigate the types of informal learning activities that novice teachers in Kuching Division, Sarawak, engaged in at work and the level of novice teachers’ engagement in informal learning activities. Specifically, this study explored the individual and organizational factors affecting novice teachers’ engagement in informal learning activities, the relationship between level of informal learning engagement and organizational culture in school, and it also investigated the differences in the level of novice teachers’ engagement in informal learning activities based on gender. This study was a cross-sectional survey research involving 85 novice teachers randomly selected from ten schools in Kuching Division, Sarawak. Findings showed that novice teachers were only moderately involved in workplace informal learning activities. The findings also showed moderate but significantly positive relationship between school culture and the level of informal learning engagement among novice teachers. However, there was no significant difference between male and female novice teachers in the level of engagement in workplace informal learning. In addition, findings also indicated that novice teachers learnt most frequently from their own trial and error activities. Novice teachers’ engagement in informal learning activities was influenced by their interest in the current professional field and job environment. The findings of this study showed that schools need to promote and support informal learning opportunities for novice teachers as such learning activities serve as important impetus for their continuous professional development.